Video stations, a potential low-cost tool to monitoring invertebrates: A pilot study with Limnephilidae (Trichoptera) - Fernández, María Valeria (2023)
The aim of this study was to evaluate the performance of Underwater Video Stations (UVS) to detect caddisfly larvae (Trichoptera), estimate density in a lake, as well as to evaluate its effectiveness in tracking larvae for future behavioural or personality studies in the natural habitat. For this, was deployed UVS. Recording a total of 3120 minutes of video were analysed, of which 968 min were used for abundance analysis. Finally, caddisfly larvae were tracked using the Tracker software, which recorded the velocity ofeveryone in mm/s. This work successfully put into practice a novel sampling methodology for this insect group. The technique was implemented quickly, easily, andinexpensively and is highly scalable for the monitoring of aquatic invertebrates. Remotevideo stations are a potential tool for use in the field of population monitoring and studiesof personality and behaviour in the natural habitat.